Penerapan Surat Edaran Kemendagri No 440/3917/SJ Tentang Percepatan Vaksinasi Dosis Lanjutan (Booster) Bagi Masyarakat di RW IV Kel. Salamanmloyo Kota Semarang - Jamil, Masfufatun (Fakultas Syariah INSURI Ponorogo, 2022)
Indonesia makes the implementation of COVID-19 vaccination as part of the strategy to overcome the COVID-19 pandemic. The government issued a regulation for the implementation of vaccination as stated in the Regulation of the Minister of Health of the Republic of Indonesia Number 10 of 2021 concerning the Implementation of Vaccination in the Context of Handling the 2019 Corona Virus Disease (COVID -19) Pandemic. Following up on the directives of the President of the Republic of Indonesia in the context of preventing and overcoming COVID-19, it is necessary to require a further dose of vaccination (booster) for people who will travel in and/or participate in activities that cause crowds. Therefore, it is necessary to accelerate the implementation of booster doses nationally through various strategies in a proactive, persuasive, focused, and coordinated manner. In this regard, a circular letter No. 440/3917/SJ is issued concerning the Acceleration of Advanced Dose Vaccination (Booster) for the Community. The approach method used is sociological juridical and the research specifications used are analytical descriptive. The juridical aspects examined are the legal provisions concerning circular letter No. 440/3917/SJ regarding the Acceleration of Advanced Dose Vaccination (Booster) as well as knowing the obstacles faced in the implementation of its application in the RW IV Kel. Salamanmloyo, West Semarang District. The sociological aspects studied were residents regarding the application of circular letter No. 440/3917/SJ concerning Acceleration of Advanced Dose Vaccination (Booster) in RW IV Kel. Salamanmloyo, Kota Semarang.